Significance of Placental Mesenchymal Stem Cell in Placenta Development and Implications for Preeclampsia - Zhang, Yang; Zhong, Yanqi; Zou, Li; Liu, Xiaoxia (Frontiers in Pharmacology, 2022)
The well-developed placentation is fundamental for the reproductive pregnancy while the defective placental development is the pathogenetic basis of preeclampsia (PE), a dangerous complication of pregnancy comprising the leading causes of maternal and perinatal morbidity and mortality. Placenta-derived mesenchymal stem cells (PMSCs) are a group of multipotent stem cells that own a potent capacity of differentiating into constitutive cells of vessel walls. Additionally, with the paracrine secretion of various factors, PMSCs inextricably link and interact with other component cells in the placenta, collectively improving the placental vasculature, uterine spiral artery remolding, and uteroplacental interface immunoregulation. Recent studies have further indicated that preeclamptic PMSCs, closely implicated in the abnormal crosstalk between other ambient cells, disturb the homeostasis and development in the placenta. Nevertheless, PMSCs transplantation or PMSCs exosome therapies tend to improve the placental vascular network and trophoblastic functions in the PE model, suggesting PMSCs may be a novel and putative therapeutic strategy for PE. Herein, we provide an overview of the multifaceted contributions of PMSCs in early placental development. Thereinto, the intensive interactions between PMSCs and other component cells in the placenta were particularly highlighted and further extended to the implications in the pathogenesis and therapeutic strategies of PE.